The Destructive Effects of Extremely Halophilic Archaeal Strains on Sheepskins, and Proposals for Remedial Curing Processes Use of sterile brine or direct electric current to prevent red heat damage on salted sheepskins - (:unkn) unknown (JOHNSON MATTHEY PUBL LTD CO, 2020)
Proteolytic and lipolytic extremely halophilic archaea found in curing salt may contaminate skins during the brine curing process and damage skin structure. In the present study, three proteolytic and lipolytic extremely halophilic archaea were isolated from deteriorated salted sheepskins and characterised using conventional and molecular methods. Each test strain (Haloarcula salaria AT1, Halobacterium salinarum 22T6, Haloarcula tradensis 7T3), a mixed culture of these strains and the mixed culture treated with 1.5 A direct current (DC) were used for brine curing processes of fresh sheepskins and examined during 47 days of storage to evaluate the degree of destruction wreaked by these microorganisms. Both organoleptic properties and scanning electron microscopy (SEM) images of sheepskins proved that each separate test strain and the mixed culture caused serious damage. However, the mixed culture of strains treated with electric current did not damage sheepskin structure. Therefore, we highly recommend sterilisation of brine using DC to prevent archaeal damage on cured hides and skins in the leather industry.
Keywords: HYPERSALINE ENVIRONMENTS; BACTERIAL-POPULATIONS; SKINS; HIDES; IDENTIFICATION; INACTIVATION; PRESERVATION